The Concentration-Profitability Relationship in Turkish Industry - Ozhan, Meral (European Journal of Economics and Business Studies, 2015)
The concept of industrial concentration refers to the control of a given industry by a small number of leading firms which are exclusively engaged in that industry. In economic theory concentration is an important concept to understand a departure away from competitive market structure which is accepted as a reference point for efficiency. Using the traditional structure-conduct-performance (SCP) paradigm many researchers found that the higher the level of concentration is the higher the level of profitability. In an earlier study I attempted to determine the level of concentration in the Turkish manufacturing industry for 84 sectors. In addition, I conducted a multiple regression analysis in various forms to identify the determinants of concentration and its effects on profitability. In most regression results, the relation between concentration and profitability was found positive and statistically significant. The present paper takes one step further and summarizes two new dimensions of industrial concentration. The first is to understand the current level of concentration for the Turkish manufacturing industry using a larger set of data. The new data set obtained from the TurkStat provides some basic statistics over the period 2009-2012 for 224 four-digit manufacturing industries. A brief analysis of the current data shows a slightly declining trend in the overall concentration ratio. CR4 (four-firm concentration ratio) fell from 51 to 49, CR8 (8-frim concentration ratio) fell from 61 to 60, and HHI (or H for short, Herfindahl-Hirschman index) dropped from 0. 173 (or from 1730) to 0. 153 (or to 1530). However a much bigger drop is observed for a longer period in the data coming from the top 500 industrial firms of ICC (Istanbul Chamber of Commerce). The latter data show a sharp fall in CR8 from 32 percent to 24 percent. These results together reflect a falling tendency in the dominant role of large firms in the Turkish economy which is a sign of increased level of competitive environment.
Keywords: concentration, profitability, relationship, Turkish, industry